2007
DOI: 10.1038/sj.bjc.6604016
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of multiple genes as clonal markers in multicentric hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is highly malignant and prone to multicentric occurrence. Differentiation between a true relapse of HCC and a second primary tumour appearing is of clinical importance. At this point, no convenient method is available to determine the origin of these HCCs. Tissue samples were obtained from 19 patients and analysed for the promoter hypermethylation status of multiple tumour suppressor genes (p16, DAP-Kinase, MGMT, GSTP1, APC, RIZ1, SFRP1, SFRP2, SFRP5, RUNX3, and SOCS1) using meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
142
3
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(153 citation statements)
references
References 13 publications
7
142
3
1
Order By: Relevance
“…Most mutations in cancers occur in the D-loop region of mtDNA. Mutations in the mtDNA D-Loop region are a useful marker for determining the cell clonal origin for multiple HCC (Nomoto et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most mutations in cancers occur in the D-loop region of mtDNA. Mutations in the mtDNA D-Loop region are a useful marker for determining the cell clonal origin for multiple HCC (Nomoto et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, in clinical practice, it is important to identify the original type of multinodular HCC preoperatively to determine the appropriate therapeutic strategy, but this is a considerable challenge. Detection of the mutations in the mtDNA D-Loop in the plasma may be useful (Nomoto et al, 2002), but further study is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial mutations are commonly found in multiple cancers types 133-137 . One advantage of mitochondrial DNA as a marker for cancer is that each cell has many more copies of the mitochondrial genome than of nuclear DNA, and the amount of mitochondrial DNA in cancer cells is several times more abundant than it is in normal tissues 133,134,136,138 . A "MitoChip" has been developed to interrogate the mitochondrial genome, 135 , and initial studies suggest that this chip can be used to detect mitochondrial mutations in pancreatic juice samples obtained from patients with pancreatic cancer 135 .…”
Section: Epigenetic Markersmentioning
confidence: 99%
“…The range of P14 and MGMT methylation in HCC tissues was 0-80% and 0-64.3% (Tannapfel et al, 2001;Yu et al, 2002;Yang et al, 2003;Yu et al, 2003;Anzola et al, 2004;Qian et al, 2005;Liu et al, 2006;Nomoto et al, 2007;Ruan et al, 2007;Lou et al, 2008;Herath et al, 2009;Li et al, 2010;Li et al, 2013), respectively, and some studies reported that the levels of methylation were higher in control than in cancer tissues (Su et al, 2007;Zhang et al, 2007;Formeister et al, 2010). Based on these inconsistent results, we performed a meta-analysis using the accumulated data to accurately assess the association between P14 and MGMT methylation and the risk of HCC.…”
Section: Introductionmentioning
confidence: 99%